PENGGUNAAN MODEL GENERATIVE LEARNING TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SMA NEGERI 1 TAPA - suma, reza ardiansyah; Sumarno Ismail, Auli Irfah, Sarson Pomalato, Hasan Panigoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to improve mathematics learning outcomes through the Generative Learning model on the topic of two-variable linear equation systems. This research is a classroom action research (PTK). The subjects of this study are students of class X-2 in the 2024/2025 academic year, totaling 28 students. Data collection techniques used were observation and tests. Data analysis techniques included analysis of teacher and student observations as well as mathematics learning test results. The research procedures included planning, implementation, observation, and reflection. The study consisted of two cycles. The Generative Learning approach on the material of two-variable linear equation systems was implemented according to the lesson plan and successfully created a conducive learning environment and improved students’ mathematics learning outcomes. The results showed that in cycle I, 50% of students were in the poor category, while in cycle II, 82% were in the good category. The observation results of the teacher’s teaching skills improved, with cycle I still at a sufficient level (C), whereas in cycle II, it reached the success indicators by achieving good (B) or very good (SB) criteria. The observation of students’ learning activities also increased, with cycle I showing fairly active (KA) criteria, while in cycle II, it reached the success indicators by achieving active (A) or very active (SA) criteria.